Effects of citrus tree-shape and spraying height of small unmanned aerial vehicle on droplet distribution - Pan, Zhang; Lie, Deng; Qiang, Lyu; Shaolan, He; Shilai, Yi; Yande, Liu; Yongxu, Yu; Haiyang, Pan (International Journal of Agricultural and Biological Engineering, 2016)
In order to explore the droplet penetration of spraying with unmanned aerial vehicle (UAV) on citrus trees with different shapes, the tests were carried out at different working heights. The material was five years old Cocktail grapefruit (Citrus paradisi cv. Cocktail) grafted on Trafoliata (Poncirus trifoliata L. Raf.) and the type of UAV sprayer used was the 3W-LWS-Q60S. A solution of 300 times Ponceau 2R diluents liquid instead of pesticide was used for citrus fields spraying and the droplets were collected by paper cards. Droplets deposition parameters were extracted and analyzed using digital image processing after scanning the cards. The results showed that: 1) For the trees with round head shape canopy, the droplet depositions of the upper, middle and lower layers had a significant difference at 0.05 level. The droplet deposition had the best effect when the working height was 1.0 m, where the average droplet deposition densities were 39.97 droplets/cm2 and the average droplet size was 0.30 mm, but the droplet coverage (3.19%) was lower than that at the working height of 1.5 m (4.27%). 2) Under three different working heights of UAV, the tree with open center shape can obtain higher droplet deposition density at all three layers than that with the round head shape canopy. It was especially prominent when the working height was 1.0 m, as the middle layer increased by 49.92%. However, the higher range of droplet deposition density meant larger fluctuation and dispersion. 3) The open center shape canopy and the 1.0 m working height obviously improved the droplet coverage rate and droplet density in the citrus plant. For these parameters of open center shape citrus tree, there was no obvious difference in the front and rear direction, but in the left and middle part of the tree crown, the difference reached a 0.05 significant level. Considering droplet deposition characteristics and the spray uniformity, the UAV performed better when working on open center shape plants at a 1.0 m working height.Keywords: citrus, tree shape, unmanned aerial vehicle (UAV), droplet depositionDOI: 10.3965/j.ijabe.20160904.2178Citation: Zhang P, Deng L, Lyu Q, He S L, Yi S L, Liu Y D, et al. Effects of citrus tree-shape and spraying height of small unmanned aerial vehicle on droplet distribution. Int J Agric & Biol Eng, 2016; 9(4): 45－52.